The Impact of Strategy on Sharing Economy Companies: Lessons for Mobike - ZHANG, Wanfu (2017)
The sharing economy is growing rapidly these years, and has changed the lifestyle of citizens that the unoccupied resources can be shared to others who are need them to create new values through the online platforms (Fang, Ye, Law 2016). People is now emphasizing on the right of use instead of the ownership, and used to the sharing taxi, short rental even the bicycles which appeared from 2016 in China (Zhou, W. 2017). The sharing bicycle is used to solve the ‘last one mile’ after the subway and the short-distance daily trip in the first and second-tier cities (Ge 2017 and Xue 2016), moreover, the most successful sharing bicycle firms now are Mobike and OFO. However, there are several problems of this industry, for example, unprofitability operation, heavy competition, no differentiation of the products, etc.. This paper has made a research with the customers of Mobike, by using interview as the methodology, in order to obtain the opinions, feelings and advices from the consumers. Besides, using the PEST analysis and two of Porter’s five forces to analyse the external and internal competitive condition and the reasons of why the industry of Mobike is unprofitability status. In addition, analysing the products, profitability strategy, brand strategy and so on of the top two famous and successful previous sharing economy firms which are Uber and Airbnb. What’s more, this paper also included the analysis of OFO the main competitor of Mobike to explore the problems of the sharing bike industry and why OFO are more popular than Mobike in some area.